Preparation method and application of Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material
By constructing Cu2O-SnO2/g-C3N4 ternary composite material, using the dual action mechanism of Z-scheme and p-n junction, the problem of low photocatalytic efficiency of existing photocatalytic materials is solved, and efficient degradation of organic pollutants in water is achieved and Good reuse properties of materials.
Patent Information
- Application Number
- CN202411135989.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-19
- Publication Date
- 2024-12-31
AI Technical Summary
When existing photocatalytic materials treat organic pollutants in water, their photocatalytic efficiency is low and difficult to effectively improve. The research on composite catalytic systems needs to be further explored to improve the separation efficiency and light absorption capacity of photogenerated electron-hole pairs.
By constructing Cu2O-SnO2/g-C3N4 ternary composite material, the dual action mechanism of Z-scheme and p-n junction is used to improve the photocatalytic performance. The preparation method includes roasting carbon and nitrogen precursor to obtain g-C3N4 powder, and synthesis and oxidation of hydrothermal reaction. The tin powder and Cu2O form a p-n heterojunction and a Z-scheme heterojunction to enhance photocatalytic activity.
The photocatalytic activity was significantly improved. The degradation rate of Cu2O-SnO2/g-C3N4 ternary composite material to methyl orange can reach 96.58% within 110 minutes, and the degradation rate remains at 90.04% after three recycling, which proves that it Highly efficient and stable photocatalytic properties.
Smart Images

Figure CN119215946A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photocatalytic materials, and in particular to a method for preparing a Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material. Background Art
[0002] With the continuous acceleration of industrialization and urbanization, environmental pollution problems have become increasingly prominent, especially the treatment of organic pollutants in water, which is a problem that needs to be solved urgently. Photocatalytic technology has broad application prospects in the field of organic pollutant treatment due to its environmental friendliness and high efficiency. However, the photocatalytic efficiency of existing photocatalytic materials still needs to be further improved due to the limitations of their own properties. Among them, the composite catalytic system composed of multiple materials has attracted much attention. The composite catalytic system not only combines the advantages of a single catalyst, but also has unique advantages in improving the separation efficiency and light absorption capacity of photogenerated electron-hole pairs. This paper focuses on the preparation of the Cu2O-SnO2 / g-C3N4 composite catalytic system and in-depth research on its photocatalytic performance, aiming to develop an efficient, stable and recyclable photocatalytic system to provide strong support for the photocatalytic treatment of organic pollutants.
[0003] The preparation of photocatalytic composite materials can greatly improve the shortcomings of single semiconductor photocatalytic materials and enhance the material's response to visible light, the separation of photogenerated carriers and the promotion of carrier migration. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing a Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material. The three materials, Cu2O, SnO2 and g-C3N4, effectively improve the photocatalytic performance by constructing a dual action mechanism of Z-scheme and pn junction.
[0005] The technical solution of the present invention is:
[0006] A method for preparing a Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material specifically comprises the following steps:
[0007] S1, the carbon-nitrogen precursor powder is calcined to obtain g-C3N4 powder;
[0008] S2, after adding g-C3N4 powder, tin oxide powder, surfactant and copper source to deionized water, stirring and mixing evenly to obtain a mixed solution, the mass ratio of g-C3N4 powder to tin oxide powder is 0.5-1.5:1, and then adding sodium hydroxide solution dropwise to the mixed solution, blue floccules gradually appear in the mixed solution, and after the sodium hydroxide solution is added dropwise, ascorbic acid is added to obtain a mixed solution;
[0009] S3. The mixed solution is subjected to a hydrothermal reaction at a temperature of 100 to 190°C and a time of 7 to 14 hours. After the hydrothermal reaction is completed, the reaction solution is cooled to room temperature and then centrifuged to obtain a precipitate. The precipitate is washed, dried and ground in turn to obtain the final product, i.e., the Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material.
[0010] The carbon-nitrogen precursor powder is at least one of melamine, urea, cyanamide, dicyandiamide and thiourea. The temperature of the carbon-nitrogen precursor powder calcination treatment is 500-750° C., and the heat preservation time of the calcination treatment is 3-5 hours.
[0011] The preparation method of the tin oxide powder is specifically as follows: dissolving a tin source in deionized water to obtain a tin ion precursor liquid, adding a sodium hydroxide solution dropwise into the tin ion precursor liquid to obtain a tin precursor mixed liquid, and then subjecting the tin precursor mixed liquid to a hydrothermal treatment at a temperature of 100 to 190° C. for 10 to 18 hours, and then cooling the suspension after the hydrothermal treatment to room temperature, and then subjecting the suspension to centrifugal separation to obtain a slurry-like white precipitate, and finally, the white precipitate is sequentially washed, dried and ground to obtain tin oxide powder.
[0012] The tin source is one of Na2SnO3, SnCl4·5H2O, SnCl4·2H2O and SnO; in the tin precursor mixed solution, the mass ratio of the tin source to the sodium hydroxide in the sodium hydroxide solution is 1:0.5-1; the drying temperature of the white precipitate is 50-80°C and the time is 4-8h.
[0013] The tin source is SnCl4·5H2O.
[0014] The copper source is CuCl2·2H2O, and the surfactant is hexadecyltrimethylammonium bromide.
[0015] In the mixed solution, the molar ratio of copper ions in the copper source, the surfactant, the sodium hydroxide in the sodium hydroxide solution, and ascorbic acid is 1:0.5-3:5-10:0.25-1.
[0016] In the step S3, the precipitate is dried at a temperature of 50 to 80° C. for 4 to 8 hours.
[0017] The Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material is used for degrading high molecular pollutants in water, and the high molecular pollutants are methyl orange.
[0018] Advantages of the present invention:
[0019] (1) The present invention prepares tin oxide powder through a tin source, and then directly mixes it with g-C3N4 powder to carry out a hydrothermal reaction. This process saves time, has simple steps, has a higher organic matter degradation effect, has cheap raw materials, and has a low preparation cost. In addition, the photocatalytic activity of the ternary composite photocatalyst material prepared by the present invention is improved by 60.36 times compared with the photocatalytic activity of the SnO2 / g-C3N4 binary composite photocatalyst material, is 1.88 times the photocatalytic activity of Cu2O-SnO2, and is 1.02 times the photocatalytic activity of Cu2O / g-C3N4.
[0020] (2) In the Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material prepared by the present invention, Cu2O and SnO2 are coupled to form a pn heterojunction, thereby improving the electron-hole separation efficiency and the photocatalytic activity, and SnO2 and g-C3N4 are coupled to form a Z-scheme heterojunction, which greatly improves the catalytic performance of the photocatalytic material. That is, the dual action mechanism of the pn junction and Z-scheme constructed by the three materials of Cu2O, SnO2, and g-C3N4 can effectively inhibit the photoautolysis of Cu2O and improve the photocatalytic performance; the ternary composite photocatalytic material prepared by the present invention can degrade 96.58% of the methyl orange water pollutant within 110 minutes; after three consecutive cycles of use, the degradation rate is still maintained at 90.04%, which proves that the ternary composite photocatalytic material has good reusability. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is a SEM image of the Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material prepared in Example 1 of the present invention.
[0022] Figure 2 This is a TEM image of the Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material prepared in Example 1 of the present invention.
[0023] Figure 3 It is the PL spectrum diagram of the Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material prepared in Example 1 of the present invention and the Cu2O, g-C3N4 and SnO2 prepared in Comparative Examples 1-3.
[0024] Figure 4 This is a degradation rate curve of methyl orange of the Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material prepared in Example 1 of the present invention and Cu2O, g-C3N4, SnO2, Cu2O / g-C3N4, Cu2O / SnO2, and SnO2 / g-C3N4 prepared in Comparative Examples 1-6.
[0025] Figure 5This is a curve diagram of the degradation rate of methyl orange under three-cycle utilization of the Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] A method for preparing a Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material specifically comprises the following steps:
[0029] S1. Place melamine in a muffle furnace and calcine at 550°C for 4 hours with a heating rate of 5°C / min. After calcination, cool the furnace and grind to obtain yellow g-C3N4 powder.
[0030] S2, weigh 1.5g of tin tetrachloride pentahydrate (SnCl4.5H2O) solid, grind it and dissolve it in 20ml of deionized water to obtain a tin ion precursor liquid, then add 15ml of a sodium hydroxide solution with a concentration of 1.333M dropwise to the tin ion precursor liquid, and then continue stirring for 30min to obtain a tin precursor mixed solution, and then move the tin precursor mixed solution into a reactor lined with polytetrafluoroethylene, and hydrothermally react at 150°C for 12h, then cool the suspension after the hydrothermal reaction to room temperature, and then centrifuge (centrifugal speed 6000r / min, centrifugal time 10min) to obtain a slurry of white precipitate, and finally wash the white precipitate three times with deionized water and anhydrous ethanol respectively, place it in a blast drying oven and dry it at 65°C for 5h, and then grind it to obtain SnO2 powder;
[0031] S3, weigh 0.05g of SnO2 powder and 0.05g of g-C3N4 yellow powder, then pour into 10mL of deionized water and stir for 30min, then add 1.822g of hexadecyltrimethylammonium bromide (CTAB) and 10ml of deionized water and continue stirring for 30min, then add 0.85g of CuCl2·2H2O and stir for 30min to obtain a mixed solution, then add 12mL of 2.5mol / L sodium hydroxide solution dropwise to the mixed solution, blue floccules gradually appear in the mixed solution, after continuous stirring for 30min, then add 25ml of 0.1mol / L ascorbic acid solution dropwise, after fully stirring for 60min, obtain a mixed solution;
[0032] S4. The mixed solution was transferred into a reactor lined with polytetrafluoroethylene, and a hydrothermal reaction was carried out at 150°C for 12 hours. After the hydrothermal reaction was completed, the reaction solution was cooled to room temperature, and then centrifuged (centrifugal speed 6000r / min, centrifugal time 10min) to obtain a precipitate. The precipitate was washed three times with deionized water and anhydrous ethanol respectively, and then placed in a forced air drying oven at 65°C for 5 hours. After grinding, the final product, i.e., Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material, was obtained.
[0033] Example 2
[0034] A method for preparing a Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material specifically comprises the following steps:
[0035] S1. Place melamine in a muffle furnace and calcine at 750°C for 3 hours with a heating rate of 5°C / min. After calcination, cool the furnace and grind to obtain yellow g-C3N4 powder.
[0036] S2, weigh 0.8g SnCl4.5H2O solid, grind it and dissolve it in 20ml deionized water to obtain a tin ion precursor liquid, then add 15ml of a sodium hydroxide solution with a concentration of 1.333M dropwise to the tin ion precursor liquid, and then continue stirring for 30min to obtain a tin precursor mixed solution, and then move the tin precursor mixed solution into a reactor lined with polytetrafluoroethylene, and hydrothermally react at 120°C for 15h, then cool the suspension after the hydrothermal reaction to room temperature, and then centrifuge (centrifugal speed 6000r / min, centrifugal time 10min) to obtain a slurry of white precipitate, and finally wash the white precipitate three times with deionized water and anhydrous ethanol respectively, place it in a blast drying oven and dry it at 80°C for 4h, and then grind it to obtain SnO2 powder;
[0037] S3, weigh 0.05g of SnO2 powder and 0.075g of g-C3N4 yellow powder, then pour into 10mL of deionized water and stir for 30min, then add 3.644g of CTAB and 10ml of deionized water and continue stirring for 30min, then add 0.85g of CuCl2·2H2O and stir for 30min to obtain a mixed solution, then add 16mL of 2.5mol / L sodium hydroxide solution dropwise to the mixed solution, blue floccules gradually appear in the mixed solution, continue stirring for 30min, then add 50ml of 0.1mol / L ascorbic acid solution dropwise, and stir well for 60min to obtain a mixed solution;
[0038] S4. The mixed solution was transferred into a reactor lined with polytetrafluoroethylene, and a hydrothermal reaction was carried out at 120°C for 15 hours. After the hydrothermal reaction was completed, the reaction solution was cooled to room temperature, and then centrifuged (centrifugal speed 6000r / min, centrifugal time 10min) to obtain a precipitate. The precipitate was washed three times with deionized water and anhydrous ethanol respectively, and then placed in a forced air drying oven at 80°C for 4 hours. After grinding, the final product, i.e., Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material, was obtained.
[0039] Example 3
[0040] A method for preparing a Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material specifically comprises the following steps:
[0041] S1. Place melamine in a muffle furnace and calcine at 500°C for 5 hours with a heating rate of 5°C / min. After calcination, cool the furnace and grind to obtain yellow g-C3N4 powder.
[0042] S2, weigh 1.2g SnCl4.5H2O solid, grind it and dissolve it in 20ml deionized water to obtain a tin ion precursor liquid, then add 15ml of a sodium hydroxide solution with a concentration of 1.333M dropwise to the tin ion precursor liquid, and then continue stirring for 30min to obtain a tin precursor mixed solution, then move the tin precursor mixed solution into a reactor lined with polytetrafluoroethylene, and hydrothermally react at 180°C for 10h, then cool the suspension after the hydrothermal reaction to room temperature, and then centrifuge (centrifugal speed 6000r / min, centrifugal time 10min) to obtain a slurry of white precipitate, and finally wash the white precipitate three times with deionized water and anhydrous ethanol respectively, place it in a blast drying oven at 55°C for 8h, and then grind it to obtain SnO2 powder;
[0043] S3, weigh 0.05g of SnO2 powder and 0.025g of yellow g-C3N4 powder, then pour into 10mL of deionized water and stir for 30min, then add 5.466g of CTAB and 10ml of deionized water and continue stirring for 30min, then add 0.85g of CuCl2·2H2O and stir for 30min to obtain a mixed solution, then add 12mL of 2.5mol / L sodium hydroxide solution dropwise to the mixed solution, blue floccules gradually appear in the mixed solution, continue stirring for 30min, then add 15ml of 0.1mol / L ascorbic acid solution dropwise, and stir well for 60min to obtain a mixed solution;
[0044] S4. The mixed solution was transferred into a reactor lined with polytetrafluoroethylene, and a hydrothermal reaction was carried out at 180°C for 8 hours. After the hydrothermal reaction was completed, the reaction solution was cooled to room temperature, and then centrifuged (centrifugal speed 6000r / min, centrifugal time 10min) to obtain a precipitate. The precipitate was washed three times with deionized water and anhydrous ethanol respectively, and then placed in a forced air drying oven at 55°C for 8 hours. After grinding, the final product, i.e., Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material, was obtained.
[0045] Comparative Example 1
[0046] The preparation method of Cu2O specifically includes the following steps: 1.822g CTAB was dissolved in 10 ml of deionized water and stirred for 30 min. Then, 0.85 g of CuCl2·2H2O was added and stirred for 30 min to obtain a mixed solution. Then, 12 mL of 2.5 mol / L sodium hydroxide solution was added dropwise to the mixed solution. Blue floccules gradually appeared in the mixed solution. After continuous stirring for 30 min, 25 ml of 0.1 mol / L ascorbic acid solution was added dropwise and stirred for 60 min. During this process, the solution changed from green to orange-yellow, and finally a brick-red suspension was obtained. The prepared brick-red suspension was transferred into a reactor lined with polytetrafluoroethylene and reacted at 150°C for 12 h. After the reaction was completed, the reaction solution was cooled to room temperature and then centrifuged (centrifugal speed 6000 r / min, centrifugal time 10 min) to obtain a solid. The solid was washed three times with deionized water and anhydrous ethanol respectively, and then placed in a blast drying oven at 65°C for 5 h. After grinding, Cu2O powder was obtained.
[0047] Comparative Example 2
[0048] The preparation of g-C3N4 powder is the same as step S1 in Example 1.
[0049] Comparative Example 3
[0050] The preparation of SnO2 powder is the same as step S2 in Example 1.
[0051] Comparative Example 4
[0052] Weigh 0.1 g of g-C3N4 powder, pour it into 10 mL of deionized water and stir for 30 min, then repeat the steps of Comparative Example 1 to finally obtain a Cu2O / g-C3N4 binary composite photocatalytic material.
[0053] Comparative Example 5
[0054] Weigh 0.1 g of SnO2 powder, pour it into 10 mL of deionized water and stir for 30 min, then repeat the steps of Comparative Example 1 to finally obtain a Cu2O / SnO2 binary composite photocatalytic material.
[0055] Comparative Example 6
[0056] Weigh 1g of SnO2 powder and 2g of melamine in a mortar, grind and mix them thoroughly, then put them into a quartz boat and distribute them evenly. Finally, place them in a muffle furnace and calcine them at 550℃ for 4h. The heating rate is set to 5℃ / min. After calcination, cool them in the furnace and grind them to obtain SnO2 / g-C3N4 binary composite photocatalytic material.
[0057] Results and performance testing:
[0058] Figure 1 This is a SEM image of the Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material prepared in Example 1. Figure 1 It can be seen that the ternary composite photocatalytic material is a composite structure of three materials: Cu2O, SnO2 and g-C3N4; among them, the dense, agglomerated spheres are SnO2, and the layered and slightly larger octahedral particles are the composite structure of g-C3N4 and Cu2O. Figure 1 It can be seen that these three materials have been well combined.
[0059] Figure 2 This is a TEM image of the Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material prepared in Example 1. Figure 2 It can be seen that polyhedral Cu2O particles and tiny spherical nano-SnO2 exist on the surface of graphite carbon nitride g-C3N4.
[0060] Figure 3 The PL spectra of the Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material prepared in Example 1 and the Cu2O, g-C3N4, SnO2 prepared in Comparative Examples 1-3 are shown in FIG. Figure 3It can be seen that the photoluminescence intensity of the Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material is lower than that of Cu2O, g-C3N4, and SnO2, and its photoluminescence signal is suppressed, indicating that the recombination process is slow, the decay lifetime of photogenerated electrons is long, and the recombination rate of electron-hole pairs is low.
[0061] Figure 4 The following is a graph showing the degradation rate of methyl orange of the Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material prepared in Example 1 and Cu2O, g-C3N4, SnO2, Cu2O / g-C3N4, Cu2O / SnO2, and SnO2 / g-C3N4 prepared in Comparative Examples 1-6. Figure 4 It can be seen that under visible light (λ>400nm), the degradation rate of methyl orange by Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material is 96.58% within 110min, which is much higher than other materials, indicating that the prepared ternary composite photocatalytic material has strong photocatalytic performance.
[0062] Figure 5 This is the degradation rate curve of methyl orange by Cu2O-SnO2 / g-C3N4 ternary composite photocatalyst at different cycle times. Figure 5 It can be seen that after three cycles (1st, 2nd, 3rd), the degradation rate can still be maintained above 90.04%, with high photocatalytic stability.
[0063] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material, characterized in that: The specific steps include: S1, the carbon-nitrogen precursor powder is calcined to obtain g-C3N4 powder; S2, after adding g-C3N4 powder, tin oxide powder, surfactant and copper source to deionized water, stirring and mixing evenly to obtain a mixed solution, the mass ratio of g-C3N4 powder to tin oxide powder is 0.5-1.5:1, and then adding sodium hydroxide solution dropwise to the mixed solution, blue floccules gradually appear in the mixed solution, and after the sodium hydroxide solution is added dropwise, ascorbic acid is added to obtain a mixed solution; S3. The mixed solution is subjected to a hydrothermal reaction at a temperature of 100 to 190°C and a time of 7 to 14 hours. After the hydrothermal reaction is completed, the reaction solution is cooled to room temperature and then centrifuged to obtain a precipitate. The precipitate is washed, dried and ground in turn to obtain the final product, i.e., the Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material.
2. The method for preparing a Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material according to claim 1, characterized in that: The carbon-nitrogen precursor powder is at least one of melamine, urea, cyanamide, dicyandiamide and thiourea. The temperature of the carbon-nitrogen precursor powder calcination treatment is 500-750° C., and the heat preservation time of the calcination treatment is 3-5 hours.
3. The method for preparing a Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material according to claim 1, characterized in that: The preparation method of the tin oxide powder is specifically as follows: dissolving a tin source in deionized water to obtain a tin ion precursor liquid, adding a sodium hydroxide solution dropwise into the tin ion precursor liquid to obtain a tin precursor mixed liquid, and then subjecting the tin precursor mixed liquid to a hydrothermal treatment at a temperature of 100 to 190° C. for 10 to 18 hours, and then cooling the suspension after the hydrothermal treatment to room temperature, and then subjecting the suspension to centrifugal separation to obtain a slurry-like white precipitate, and finally, the white precipitate is sequentially washed, dried and ground to obtain tin oxide powder.
4. The method for preparing a Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material according to claim 3, characterized in that: The tin source is one of Na2SnO3, SnCl4·5H2O, SnCl4·2H2O and SnO; in the tin precursor mixed solution, the mass ratio of the tin source to the sodium hydroxide in the sodium hydroxide solution is 1:0.5-1; the drying temperature of the white precipitate is 50-80°C and the time is 4-8h.
5. The method for preparing a Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material according to claim 4, characterized in that: The tin source is SnCl4·5H2O.
6. The method for preparing a Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material according to claim 1, characterized in that: The copper source is CuCl2·2H2O, and the surfactant is hexadecyltrimethylammonium bromide.
7. The method for preparing a Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material according to claim 1, characterized in that: In the mixed solution, the molar ratio of copper ions in the copper source, the surfactant, the sodium hydroxide in the sodium hydroxide solution, and ascorbic acid is 1:0.5-3:5-10:0.25-1.
8. The method for preparing a Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material according to claim 1, characterized in that: In the step S3, the precipitate is dried at a temperature of 50 to 80° C. for 4 to 8 hours.
9. An application of a Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material, characterized in that: The Cu2O-SnO2 / g-C3N4 ternary composite photocatalytic material is used for degrading high molecular pollutants in water, and the high molecular pollutants are methyl orange.
Citation Information
Patent Citations
Cu2O / SiC / g-C3N4 ternary composite material as well as preparation method and application thereof
CN117884167A
A hybrid ternary photocatalyst for the rapid treatment of water contaminated with rhodamine b dye
IN201911011873A
Z-scheme type photocatalytic system
JP2020179346A
Cited By
Copper-tin metal oxide composite electrocatalyst for efficient ammoxidation and preparation method of copper-tin metal oxide composite electrocatalyst
CN121087547A
A copper-tin metal oxide composite electrocatalyst for efficient ammonia oxidation and a preparation method thereof
CN121087547B